Microwave and ultrasound-assisted transesterification of microalgae using homogenous and heterogeneous alkali catalyst - Cercado, Alberto Paulo I.
Novel catalysts were prepared and investigated in this study in the transesterification of microalgae for biodiesel production. The impregnation method was used to synthesize the catalysts Li-pumice, K-pumice, and Na-pumice. The synthesis parameters were varied at three different alkali solutions and solution concentrations to determine which will create the best performing catalyst in the transesterification process. The performance was measured in terms of the biodiesel yield produced in each run. Transesterification of microalgae were also made using homogeneous catalysts so that comparison can be done with that of the synthesized catalyst. Fuel properties of biodiesel produced in each study phases were also measured and compared to the regular commercial diesel in reference to the standards set by ASTM. The study was performed in five phases namely; Phase l) Transesterification of Microalgae Using Homogenous Alkali Catalyst; Phase 2) Synthesis of the alkali solid catalyst; Phase 3) Transesterification of microalgae using the Synthesized Catalyst; Phase 4) Microwave-Assisted Transesterification of microalgae; and Phase 5) Ultrasound-Assisted Transesterification of microalgae. It was proven that pumice can be made as a good catalyst support for transesterification processes. The biodiesel produced using the synthesized catalysts were in consonance with the parameters set by ASTM for biodiesel standards. The synthesis of K-pumice and Na-pumice was effective in transesterification processes creating biodiesel with FAME yield up to 85% when assisted by either ultrasound or microwave. Not only microwave or ultrasound increased the FAME yield of biodiesel produced by at least 8% but decreased the reaction time by at least 12 times. The best process parameters taken achieving the best FAME yield using K-pumice as catalyst were; (when using ultrasound) methanol to oil ratio = 12:1; catalyst load = 10%; reaction time = 10 minutes; and ultrasonic processor percent amplitude = 40%; and (when using microwave) methanol to oil ratio = 12:1; catalyst load = 10%; reaction time = 8 minutes; and microwave output power = 600 watts.